Odpowiedzi

Najlepsza Odpowiedź!
2009-11-11T22:11:23+01:00
A) x³+4x = x(x²+4) = x(x+2)(x+2)
b) x²-3x-4 = x(x-3)-4
c) 8x³-27 = (2x-3)³ = (2x-3)(2x+3)(2x+3)
d) 3x³-2x²+3x-2 = 3x(x²+1)-2(x²+1) = (3x-2)(x²+1)=(3x-2)(x+1)(x+1)
e) x⁶+7x³-8 = x³(x³+7)-8
f) x³-4x = x(x²-4) = x(x+2)(x-2)
g) 4x²-1 = (2x-1)(2x+1)
h) x³+27 = (x+3)³ = (x+3)(x+3)(x+3)
i) x⁵-2x³-x²+2 = x²(x³-1)-2(x³-1) = (x²-2)(x-1)(x+1)(x+1)
j) 3x³-2x²-6x+4 = 3x(x²-2)-2(x²-2) = (x²-2)(3x-2) = (x-√2)(x+√2)(3x-2)
k) x²-4x+4 = (x-2)² = (x-2)(x+2)
l) 12x³-3x = 3x(4x²-1) = 3x(2x-1)(2x+1)
m) x²(x-2)-3(x-2) = (x²-3)(x-2) = (x-√3)(x+√3)(x-2)
n) x⁴-5x²+4 = x²(x²-5) + 4
o) x⁴-x³-2x² = x²(x²-x-2)
1 5 1
2009-11-11T22:29:39+01:00
A) x³+4x=x(x²+4)
b) x²-3x-4=x(x-3)-4
c) 8x³-27=
d) 3x³-2x²+3x-2=3x(x+1)-2(x²+1)
e) x6+7x³-8=
f) x³-4x=x(x²-4)
g) 4x²-1=
h) x³+27=
i) x5-2x³-x²+2=x(5-2x²-x)+2
j) 3x²-2x²-6x+4=x²(3-2)-2(3x-2)
k) x²-4x+4=(x-2)²
l) 12x³-3x=3x(4x²-1)
m) x²(x-2)-3(x-2)=(x²-3)(x-2)²
n) x4-5x²+4=x(4-5x)+4
o) x4-x³-2x²=x(4-x²-2x)